Strong anisotropic spin-orbit interaction induced in graphene by monolayer WS - Wakamura,T; Reale,F; Palczynski,P; Gueron,S; Mattevi,C; Bouchiat,H (Physical Review Letters, 2018)
We demonstrate strong anisotropic spin-orbit interaction (SOI) in graphene induced by monolayer WS. Direct comparison between graphene-monolayer WS2 and graphene-bulk WS systems in magnetotransport measurements reveals that monolayer transition metal dichalcogenide can induce much stronger SOI than bulk. Detailed theoretical analysis of the weak antilocalization curves gives an estimated spin-orbit energy (Eso) higher than 10 meV. The symmetry of the induced SOI is also discussed, and the dominant z → −z symmetric SOI can only explain the experimental results. Spin relaxation by the Elliot-Yafet mechanism and anomalous resistance increase with temperature close to the Dirac point indicates Kane-Mele SOI induced in graphene.